Familiarity and Desire to Perceive Medical Education Courses among School Students in India- A Pilot Study - Nirmal Famila Bettie; Keerthi Narayan.V; Rathika Rai; Mugesh Raj; Karthikeyan; Mohamed Azarutheen (Indian Journal of Forensic Medicine & Toxicology, 2021)
The number of dentist serving the rural areas is relatively low and the practice of seeking general physiciansfor dental treatments can still be evident in areas where dental services are not accessible. But it is unclearwhether students from suburban regions prefer to pursue dentistry as their first choice of preference. Hence,the present study was aimed to find the interest in dentistry among the aspiring school students, to evaluate ifthe existing exams remain a challenge, from choosing a medical course, and also to assess if the emergenceof COVID-19 has actually increased the popularity of traditional medicines. A survey questionnaire with16 questions was shared through online media to 200 school students both in urban and suburban regionsafter validation for this pilot study. After consent to participate, the responses collected were tabulated andstatistically analyzed. It was observed that only 64% (urban) and 73% (suburban) were aware of dentistrywith a slight increase in student’s choice for traditional medicine courses over allopathic medicine (40%urban, 48% suburban) post pandemic. Within the limitations of this study it is evident that school studentsare less aware of various dentistry courses, and access to training for the exams can motivate the number ofstudents seeking admission to dentistry courses.